Diversity and density of tea pests in the tea gardens of Manipur - R. Varatharajan, K. Dhanapati Devi, K. Nishikanta (Journal of Plantation Crops, 2016)
Twenty one species of tea pests have been recorded for the first time from the tea gardens of Manipur which include twelve species of cutting and chewing pests, seven species of sucking pests, a stem borer and a leaf miner. Among them, red spider mite, (Oligonychus coffeae), leaf roller, (Caloptilia theivora), thrips (Mycterothrips setiventris) and aphid, (Toxoptera aurantii) were categorised as important pests and the rest as minor pests based on the observations carried out for one pruning cycle during 2010 to 2013. Field studies had shown that red spider mite (RSM) infested the tea plants all through the year with peak density of 16 mites per leaf per bush in April, whereas occurrence of thrips had been recorded with maximum abundance of 6 thrips per leaf per bush during October. On the other hand, tea aphids infested the plant from March to October with maximum of 200 individuals per 5 cm length of tea shoot in September. The stem borer,Â Zeuzera coffeae was noticed during March, April and September with an average density of 9.5 borers per 40 bushes. Among the foliage folders, leaf roller was predominant over flush worm and tea tortrix. Occurrence of leaf rolls was noticed from June to November with maximum incidence of 6 larvae per bush in October, but flushworms and tortrix were abundant even in April with the mean of 3 larvae per infested tea bush. Based on the above observation, a pest calendar was prepared for the tea pests of Manipur for planning pest control measures. Besides, 16 species of natural enemies attacking the tea pests are also reported in this article.